Eels of the genus Bathyuroconger in the northwestern Pacific, with descriptions of four new species (Anguilliformes: Congridae) - Smith, David G.; Ho, Hsuan-Ching; Tashiro, Fumihito (Zootaxa, 2018)
Examination of the congrid genus Bathyuroconger in the northwestern Pacific reveals six species are present. Bathyuroconger albus sp. nov. differs from congeners in having a pale coloration, a moderately reduced gill opening that is close to but not touching the pectoral-fin base, trunk length 2.0–2.9 times HL, preanal vertebrae 45–54, preanal lateral-line pores 42–48. Bathyuroconger dolichosomus sp. nov. has a moderately reduced gill opening that is close to but not touching the pectoral-fin base, trunk length 3.2 times HL, preanal vertebrae 63, and preanal lateral-line pores 61. Bathyuroconger fowleri sp. nov. has a small gill opening distant from the pectoral-fin base, trunk length 1.7–2.1 times head length, dorsal-fin origin over middle of pectoral fin, predorsal vertebrae 10–14, preanal vertebrae 48–52, total vertebrae 173–178. Bathyuroconger hawaiiensis sp. nov. has a slightly reduced gill opening, separated from the pectoral-fin base, dark color, total vertebrae 201–210. Bathyuroconger parvibranchialis (Fowler, 1934), redescribed herein, has a small gill opening distant from the pectoral-fin base, dorsal-fin origin over base of pectoral fin, trunk length 1.4–1.7 times in HL, preanal vertebrae 43–48, total vertebrae 181–189, and a uniformly dark color in adults. Bathyuroconger cf. vicinus has a full-size gill opening in contact with pectoral-fin base, dark color, and total vertebrae 196–201. A key to the species in the northwestern Pacific is provided.